The secret in the old attic. - Keene, Carolyn (New York Grosset & Dunlap, 1970)
Nancy Drew must use clues in a dead man's letters to find some unpublished musical manuscripts that will save an old man and his granddaughter from financial ruin.
Keywords: Mystery and detective stories